Lived Experiences of School Leaders in Integrated School: Milagros Context - Baby Jane A. Bayola; Maryrose D. Logronio; Delon Angelo L. Dela Cruz (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
The present study is a phenomenological study which aimed to explore the lived experiences of the school leaders in the management of Integrated Schools in Milagros, Masbate in terms of their positive experiences, challenges faced and coping strategies. The study used a qualitative approach, grounded in Transformational Leadership Theory, Distributed Leadership Theory and Phenomenological Theory. The data was obtained by using the semi-structured interviews and survey questionnaire checklists to the purposively selected school leaders of the Magsalangi Integrated School, the Matiporon Integrated School and the John Miller Integrated School. Thematic analysis was used to analyze the collected data. The results showed that school leaders felt fulfilled with the successful implementation of school projects, working with stakeholders and professional development. They also faced problems in financing, allocation of resources, workload management, and managing both the elementary school and the secondary school at the same time. School leaders responded to these issues by working collaboratively, communicating effectively and taking responsibility together. The study concludes that integrated schools’ leaders need to be resilient, adaptable and practice collaborative leadership. It suggests release of school funds in time, giving extra administrative support, better school community cooperation, optimized school resources utilization, and further research on the integrated school leadership.